Carbon Dioxide Removal Using Blended Amine Solution in a Randomly Packed Bed Column - Dhuyool, Amjad W.; Shakir, Ibtehal K.; Al-Lami, Munaf (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Many researchers are currently investigating carbon dioxide capture and storage since it is suppressing the global warming phenomenon. Aqueous carbon dioxide chemical absorption is the most effective method. The present study incorporates the applicability and performance of blended alkanol amine solutions monoethanolamine (MEA) with diethylenetriamine (DETA) as a chemical blended absorbent investigated in a pilot scale column packed randomly with Rashing rings. The effect of operating conditions on absorption performance was examined. The performance investigation is given in terms of the overall mass transfer coefficient  and carbon dioxide capture efficiency (ƞ). Typically, DETA: MEA with a mass ratio of 1:1 and total mass concentration of 30 % wt.  could provide the highest KGav with a value of 0.1572 (kmol/(m3*Kpa*hr)) and ƞ with a value of 98.79 %. While at the same condition in terms of liquid and gas rate, with DETA: MEA in the blending mass ratio 0.25:1, the KGav and ƞ values equal to: 0.1198 (kmol/(m3*Kpa*hr)) and 96.37%, respectively. Based on these findings, it is reasonable to assume that diethylenetriamine, a solution of alkanol amines, would serve as an efficient blending absorbent for carbon dioxide removal.